Analisis Bibliografi Koleksi Perpustakaan Nasional Republik Indonesia Terkait Palestina-Israel - Nasution, Muhammad Ansyari Tantawi; Zahra, Siti Fatimatuz (Media Pustakawan, 2024)
This research aims to carry out bibliographic analysis based on scientific subject, creator, year of publication and author as well as filtering relevant works from the collections held by the National Library of Indonesia related to the Palestine-Israel conflict.  The keywords used are "Aqsa, Gaza, Israel, Jews, Jews, Palestine, Palestine, West Bank, Jews, West Bank, Zionist, Zionist". The total data obtained and processed was 1638 from the National Library of Indonesia's Integrated Library System (INLIS). The method used is the bibliographic analysis where the processed data is then displayed in the form of tables and diagrams and explained with narratives that have been linked based on theory. The results of research found that the subject whose use was quite high 13 times was Zionism. The subject of Zionism is more influential than the subject of Israel in the theme of the Palestinian-Israeli conflict. The National Library of Indonesia collects many United Nations (UN) publications on this theme. Apart from that, the oldest book collection owned by National Library of Indonesia regarding the Palestinian-Israeli conflict comes from 1848 and the newest is from 2024. The conclusion obtained shows that National Library of Indonesia does not have ideological interests, this is proven by the balanced subject between Palestine and Israel. However, the National Library of Indonesia has a constitutional interest in procuring this collection, as can be seen from the many publications from the UN related to this issue.